Створення високопористого вогнетривкого теплоізоляційного матеріалу - Павленко, Анатолій Михайлович; Яковлєва, Ірина Геннадіївна; Чейлитко, Андрій Олександрович; Матказіна, Римма Ринатівна (НТУ "ХПІ", 2017)
У статті розглядається створення високопористого вогнетривкого теплоізоляційного матеріалу шлікерним методом. Створено вогнетривку пустотілу високопористу цеглу та цеглу з закритими порами розмірами 4х15х15мм з більш високими експлуатаційними характеристикам ніж звичайні вогнетриви. Дослідження, проведені авторами, також підтверджують можливість створення якісного пористого вогнетриву генезисом деструкції, що дасть можливість отримати мінімальну можливу теплопровідність для вогнетривів в межах 0,047Вт/(м∙К).

The development of new refractories with improved characteristics is an important task of energy. The purpose of the study is to determine effective parameters for the porosity of refractory in which it is possible to obtain a minimum conductivity. Elected of technology and its heat treatment for quality refractory bricks. The article discusses the improvement of the thermophysical properties of refractories due to the structuring of large pores (voids). Created of highly refractory bricks and hollow bricks with closed pore size 4x15x15 with higher performance characteristics than conventional refractories. Shows the layout of holes (voids) in the bricks which help to reduce weight and lower thermal conductivity characteristics. Research conducted by the authors also support the ability to create high-quality porous refractory genesis of destruction that will result in minimum possible thermal conductivity for refractories within the 0,047 Vt / (m ∙ K). The thermal conductivity of the obtained bricks below the thermal conductivity of the same brick without holes. The resistance has not changed and remained high. The compressive strength is 15% below the compressive strength of the bricks without holes.
Creation highly porous refractory insulation material
Keywords: теплоенергетика; вогнетрив; шлікерний метод; коефіцієнт теплопровідності; insulation material; refractory; Schlicker method; coefficient of thermal conductivity